Transformational Leadership and Team contentment A case of two teams in a Sri Lanka based Multinational Organization - Jayasuriya, C.P (Masters of Arts in Labour Studies, 2008)
e concept of leadership is a widely discussed phenomenon today at various forums. Globalization and the boundary free business environment that exist today have led the way to rigorous competition and difficulty in survival for every organization, whether large or small scale, private or government, multinational or national. These changes and challenges have brought about the need for new trends in leadership, which encompasses goal orientation, employee motivation, development, with employee contentment. Among the various styles of leadership that are being discussed and practiced, transformational leadership has become an important leadership style due to its potential to accommodate the complexities found in a technologically advanced, dynamic, and multinational work environments of today. Although the idea of transformational leadership has gained access to management discussions in the 80's with personalities such as Bass (1985) and Bums (1978), it has become more valid today, especially in the context of multinational organizations. The essence of transformational leadership is to build commitment on the part of followers to achieve organizational objectives, empowering them to accomplish theirs with satisfaction. This research endeavours to ascertain the leadership styles employed by two group leaders of a multinational organization in Sri Lanka and to ascertain whether such leadership styles have similarities to that of transformational leadership. In addition to these core objectives the study also tries to determine the impact of such leadership styles on team contentment and how the background of the leaders affects the leadership styles.